2020
DOI: 10.1080/2162402x.2020.1747731
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressive phenotype of tumor-infiltrating neutrophils is associated with obesity in kidney cancer patients

Abstract: Infiltrating tumor neutrophils and myeloid-derived suppressor cells represent major populations in the tumor microenvironment that contribute to tumor progression. However, the phenotype of circulating and tumor-associated neutrophils, and the impact of cancer patients' metabolic state on neutrophil function need further characterization. Here we show that in kidney cancer patients, circulating neutrophils display an altered immature-like phenotype, and an activated/primed metabolic state. Circulating immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Moreover, previous studies have recognized that inflammation in tumor microenvironment plays crucial roles in tumor cell survival, proliferation, and migration. [26][27][28][29] Neutrophils enhance tumor angiogenesis by releasing proinflammatory cytokines and matrix metal-loproteinase9 (MMP9). In addition, neutrophils restrain antitumor immune by releasing argininase 1 to inhibit T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have recognized that inflammation in tumor microenvironment plays crucial roles in tumor cell survival, proliferation, and migration. [26][27][28][29] Neutrophils enhance tumor angiogenesis by releasing proinflammatory cytokines and matrix metal-loproteinase9 (MMP9). In addition, neutrophils restrain antitumor immune by releasing argininase 1 to inhibit T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-metastatic and proangiogenic role of TANs is mainly due to its capacity to secrete several proangiogenic or immunosuppressive molecules, such as VEGF, IL-1β, TGFα, FGF2; enzymes involved in ECM remodeling such as MMP9 and several chemokines (i.e., CXCL1, CCL3, CCL4, CXCL8, CXCL9 and CXCL10) [66]. In obese patients diagnosed with kidney cancer, the increased expression of arginase-1 was involved in T cell suppression [67]. Several evidence showed the presence of inflammatory CD66b+ neutrophils in both TME and peripheral blood in cancer patients and correlate their presence with poor clinical outcome [68,69].…”
Section: Tumor Microenvironment Crosstalkmentioning
confidence: 99%
“…autoimmune disease [16,17], and cancer [18][19][20], with sepsis being perhaps the most extreme pathological case for changes and creation of circulating neutrophil subsets that can be linked to sepsis outcomes [14]. However, changes in conventional neutrophil maturity/ ontogeny markers [21,22] are also seen during priming, transmigration, and activation, which have been linked to functional responses or disease states [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally considered to be just short‐lived cells that are pre‐programmed to carry out the above functions before undergoing apoptotic clearance, neutrophils have recently been recognized for their capacity to extend their lifespan [3] and display profound transcriptional plasticity, leading to the acquisition of novel functions such as the modulation of adaptive immunity [4–7]. Key studies have identified novel activation marker expression or preferential activity of neutrophil subsets in response to infection [8–12], sepsis [13–15], autoimmune disease [16, 17], and cancer [18–20], with sepsis being perhaps the most extreme pathological case for changes and creation of circulating neutrophil subsets that can be linked to sepsis outcomes [14]. However, changes in conventional neutrophil maturity/ontogeny markers [21, 22] are also seen during priming, transmigration, and activation, which have been linked to functional responses or disease states [23, 24].…”
Section: Introductionmentioning
confidence: 99%